The Phenomenon of Seasonal Beggars in The Month of Ramadan: An Islamic Economic’s Perspective - Tira Nur Fitria; Sumadi Sumadi; Indra Lila Kusuma (ITB AAS INDONESIA Surakarta, 2022)
Ramadan is the holy month for Muslims. A month full of wisdom, blessings, and forgiveness. In this month of Ramadan, Allah promises multiple rewards. Therefore, Muslims are competing in pursuing goodness, blessings, and forgiveness. Giving alms in the month of Ramadan is noble worship and the right of everyone. However, someone's generosity is often abused by certain people. This culture can become a social disease in the month of Ramadan. But behind this blessing of Ramadan, certain parties take advantage of the momentum to reap the benefits. One of them is the number of monthly beggars in the month of Ramadan. Beggars are mushrooming in public places. Islam does not make begging by lying and cheating. The reason is not only because they violate sins, but also because these actions are considered to pollute good deeds and rob poor people who need help. It even damages the good image of the poor who do not want to beg and those who love virtue. Many propositions explain the haram of begging by deception and without an urgent need. The Prophet Muhammad SAW in his hadith advises us to try and earn a living in whatever form, as long as it is lawful and good, there is no syubhat, no prohibition, and not by begging. We are also singled out for ta'affuf (taking care of ourselves from begging. We must believe that only Allah hears our troubles. As for humans, they don't like hearing about other people's troubles. Islam encourages us to strive, based on the verses and hadiths of the Prophet.